Laser Irradiation-Hindered Growth of Small-Diameter Single-Walled Carbon Nanotubes by Chemical Vapor Deposition. (27th May 2019) - Fu, Yunlei; Zhang, Xiuyun; Lao, Chunfeng; Shang, Danhong; He, Maoshuai
Abstract : SWNTs are synthesized on a Co/MgO catalyst using "laser-disturbed" CVD with CO as the carbon source. Compared with SWNTs grown by thermal CVD without laser irradiation (normal CVD), SWNTs synthesized under laser irradiation demonstrate the suppression of small-diameter SWNT growth, as indicated by Raman spectroscopy. Such a phenomenon is also observed for other supported catalysts, such as Co/SiO2 and Fe/MgO. Controlled experiments were carried out to clarify the effects of lasers. On the one hand, laser irradiation increases the reaction temperature locally, favoring the growth of SWNTs at a set temperature as low as 350°C. On the other hand, laser irradiation inhibits the nucleation of small SWNT caps, leading to the growth of large-diameter SWNT species. This work opens a new avenue for growing SWNTs with controlled diameters.